2020
DOI: 10.1002/saj2.20001
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability and agreement between methods for determining the Atterberg limits of fine‐grained soils

Abstract: The Atterberg limits (plastic limit [PL] and liquid limit [LL]) of fine‐grained soils are important for civil engineering and agronomic applications. Several methodologies exist to determine the PL and LL, each with associated merits and shortcomings. The reproducibility and uncertainties associated with the various methods have not been evaluated for different samples that differ in terms of clay mineralogy and geologic origin. The objectives were to (i) assess the repeatability of two methods each for determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…The Bobrowski and Griekspoor [44] test method utilizes a rolling device comprising two acrylic flat plates covered with unglazed paper, downward force being simultaneously applied (via the top plate) to the soil thread with the back and forth rolling motion, until the top plate comes into contact with 3.2 mm-deep side rails. Despite Bobrowski and Griekspoor [44] claiming that PLs are obtained in a more expeditious and uniform fashion, their experimental findings along with those of Rashid et al [51], Ishaque et al [52] and Rehman et al [53] independently indicated that the water contents for the thread crumbling condition obtained using this plate rolling device (i.e., PL PRD ) generally underestimate their PL HR values. It has been suggested that this most likely occurred because the paper attached to the flat plates tends to produce inhomogeneity of the soil thread, the outside becoming drier than its core, during the rolling out procedure [13].…”
Section: Proposed Alternative Pl Hr Methods Based On Onset Of Brittlenessmentioning
confidence: 88%
See 1 more Smart Citation
“…The Bobrowski and Griekspoor [44] test method utilizes a rolling device comprising two acrylic flat plates covered with unglazed paper, downward force being simultaneously applied (via the top plate) to the soil thread with the back and forth rolling motion, until the top plate comes into contact with 3.2 mm-deep side rails. Despite Bobrowski and Griekspoor [44] claiming that PLs are obtained in a more expeditious and uniform fashion, their experimental findings along with those of Rashid et al [51], Ishaque et al [52] and Rehman et al [53] independently indicated that the water contents for the thread crumbling condition obtained using this plate rolling device (i.e., PL PRD ) generally underestimate their PL HR values. It has been suggested that this most likely occurred because the paper attached to the flat plates tends to produce inhomogeneity of the soil thread, the outside becoming drier than its core, during the rolling out procedure [13].…”
Section: Proposed Alternative Pl Hr Methods Based On Onset Of Brittlenessmentioning
confidence: 88%
“…Ishaque et al [52] also reported that this method is not a workable means for 'non-cohesive' (i.e., silt) soils. However, given the relatively small number of fine-grained soils examined in each of the Bobrowski and Griekspoor [44], Rashid et al [51], Ishaque et al [52] and Rehman et al [53] studies, the author of this paper believes it would be worth revisiting, and judging the PL PRD reliability/repeatability, with respect to the PL HR , based on statistical analysis of these combined PL PRD datasets.…”
Section: Proposed Alternative Pl Hr Methods Based On Onset Of Brittlenessmentioning
confidence: 99%
“…A detailed description of the assembled database is presented in Table 1. The database consisted of 51 PL RT -PL BG data pairs sourced from the research literature (designated by Test IDs S1-S51) [52,[63][64][65], as well as original test results of nine fine-grained soils investigated by the authors (Test IDs S52-S60). As demonstrated in Table 1, the database soils, in addition to their geographical diversity, cover reasonably wide ranges of surface texture, plasticity and mineralogical properties-that is, f clay (<2 µm) = 8.9-59.5%, f silt (2-75 µm) = 7.0-72.7%, LL FC = 24.6-141.1%, PL RT = 11.9-53.4%, PI FC-RT = LL FC − PL RT = 8.1-101.6%, and A FC = PI FC-RT /f clay = 0.49-1.85 (where f clay , f silt , LL FC , PL RT , PI FC-RT and A FC denote clay content, silt content, BS fall-cone liquid limit, standard rolling-thread plastic limit, plasticity index deduced from the FC and RT test results, and soil activity index, respectively).…”
Section: Database Of Pl Rt -Pl Bg Testsmentioning
confidence: 99%
“…Following the BA framework, the 95% lower and upper agreement limits between the PL BG and PL RT can be, respectively, defined as LAL = µ D − 1.96 σ D and UAL = µ D + 1.96 σ D (where µ D and σ D denote the arithmetic mean and standard deviation of the D BA = PL BG − PL RT data, respectively). Note that the calculated LAL and UAL must be examined against an inductively-defined limit, often selected as the highest possible (water content) difference/variation in the standard measurement method (i.e., PL RT ) based on its repeatability [65]. A review of the research literature indicates that the maximum variation in the PL RT for a given fine-grained soil (accounting for measurement variations across multiple operators) can be conservatively taken as ±8% [34].…”
Section: Statistical Appraisal Of the Pl Rt -Pl Bg Relationshipmentioning
confidence: 99%
“…The Bland-Altman method is widely used in medicine (e.g., [42][43][44]) and in some satellite research [45,46]. More recent studies showed usefulness of this approach to quantify pure effects of agricultural practices on crop yield and soil physical properties [47,48] and the agreement between methods for determining the Atterberg plastic and liquid limits of soils [49]. This study was inspired by recent literature reviews indicating that, despite their importance, sandy soils have received less research attention compared to other soils [1,5].…”
Section: Introductionmentioning
confidence: 99%